Strategies Of Language Police In Online Discourses - Sumartini (Institut Pendidikan Alfatah Mataram, 2026)
The development of digital technology has transformed human communication patterns from predominantly face-to-face interactions into text-based communication within virtual spaces. Online discourse through social media, discussion forums, and digital communication platforms frequently generates ethical challenges, particularly concerning language politeness. This study aims to analyze politeness strategies used in online discourse and identify the factors that influence their use. The study employs a qualitative approach with a pragmatic discourse analysis method. Data were collected from user comments on social media platforms, including Instagram, Twitter/X, and YouTube, particularly comments discussing public issues. The data were analyzed using Brown and Levinson’s theory of politeness strategies and Leech’s politeness principle. The findings indicate that positive politeness strategies are the most dominant strategies used in online discourse, particularly to establish solidarity, social closeness, and a sense of belonging among communication participants. Negative politeness strategies were also identified, including the use of indirect expressions, apologies, and strategies for avoiding potential conflicts. However, several violations of politeness principles were also found, particularly in interactions characterized by anonymity, strong emotional expression, and polarization of opinions. These findings demonstrate that although digital spaces provide broad opportunities for freedom of expression, politeness norms continue to play an important role in maintaining harmonious communication. The study contributes to the field of digital pragmatics and provides practical insights for strengthening digital literacy and promoting ethical communication practices in online environments.